Strategi Pemasaran Kopi Spectrum di Kota Bogor - Puji Nurul Hikmah; Wahyu Budi Priatna (Forum Agribisnis, 2020)
The gaining of society’s enthusiasm for coffee can be seen from the increased number of coffee consumption in Indonesia. This would be an opportunity for an entrepreneur to open a coffee shop. The number of coffee shops has always increased from year to year, especially in Bogor City as one of the tourism cities in Indonesia. In this situation, the level of competition will surely increase. Therefore, effective alternative strategies are needed to succeed in this competition. The purpose of this research is to identify the internal and external environmental factors of the company to formulate the priorities of the right marketing strategies. The methods used in this research are the IFE matrix, EFE matrix, IE matrix, SWOT matrix, and QSPM (Quantitative Strategic Planning Matrix). The result of the analysis shows that Kopi Spectrum is in a position of growth and build. Five marketing strategies generated from SWOT Matrix Analysis, that can be implemented by Kopi Spectrum, maintain product quality with an appropriate price (SO1), improve promotional activities that are suitable for the targets (WO1), expand a network of suppliers (ST1), maintain the number of consumers they already have with services and facilities (ST2), and get the halal certificate (WT1). Based on QSPM calculations, the priority strategy from Kopi Spectrum is to maintain the number of consumers they already have with services and facilities.